Moduli spaces of Higgs bundles: old and new - Swoboda, Jan (Jahresbericht der Deutschen Mathematiker-Vereinigung, 2021)
We give an overview of the differential geometric and analytic aspects of Higgs bundles and their moduli spaces and highlight some of their interrelations with neighboring ﬁelds. We review various current developments in this subject and provide a discussion of a number of open problems.
Gesehen am 07.08.2023